(untitled) (Iraqi Journal of Medical Sciences, 2020)
Nanoparticle is an artificial cell-like particle (antigen-presenting artificial cell that can be tuned to target a specific disease or infections). The outer surface of each particle is covered with universal adaptor molecules having attachment points for antigens, specific molecules on specific cells, and fight off the targeted disease. Inside of each particle, there is either cytokines, cytotoxic drugs, antimicrobial drugs, genetic material, iron, gold, herbs, and others; each for different curative purpose, yet all of them act locally with high specificity to avoid devastating side effects of the contents if given systemically or to target certain tissue for curing diseases due to genetic deletions, or as a vaccine. Different nanoparticles differ in size, shape, contents, material of the outer shell, and purpose (i.e. for diagnosis of cancer, fighting that cancer, dealing locally with autoimmune diseases, treating a disease with genetic deletion mutations, fighting an infection, monitoring, and control of biological systems. Keywords:Nanoparticles, diagnostic tool, therapeutic applications Citation:Abdul Kareem IA, Hamzah MI. Nanoparticles technology in medicine, as a diagnostic tool, and therapeutic applications for many chronic and genetic diseases: A review. Iraqi JMS. 2019; 17(3&4): 238-253. doi: 10.22578/IJMS.17.3&4.11